Evaluation of Plasma Selenium Level and its Association with Malnutrition in Hemodialysis Patients in Golestan Province, Iran - Saeed Amirkhanlou; Hassan Emadi; Anna rashedi; Samira Eshghinia (Golestan University Of Medical Sciences, 2017)
ABSTRACT Introduction: Selenium (Se) is a rare element with well-demonstrated anti-oxidative effects that acts as an enzyme co-factor in physiological interactions. Low plasma Se level and malnutrition in hemodialysis (HD) patients could increase the risk of morbidity and mortality among these patients. Moreover, Se deficiency leads to oxidative stress and inflammatory response. Therefore, this study aimed to determine the association of plasma Se levels with malnutrition and inflammatory markers in HD patients. Materials and Methods: This cross-sectional study included 88 patients undergoing routine HD at dialysis unit of 5th Azar Hospital in Gorgan, northeastern Iran. In addition, 88 healthy individuals were selected from the patients’ families as controls. Level of Se, C-reactive protein (CRP), low-density lipoprotein (LDL), high-density lipoprotein (HDL), triglyceride (TG) and albumin were measured in the patients and controls by the atomic absorption method. Se levels were categorized into two groups of "over half-normalized" and "under half-normalized" for further analysis. Results: Hyposeleniemia was found in two patients (2.3%). The mean level of Se in HD patients was lower than in the healthy controls (P< 0.001). Among all HD subjects, 30.3% had under half-normalized Se level. In addition, 79.5% of HD patients were well nourished and 20.5% were moderately malnourished. There was no statistically significant difference between the mean level of Se in the malnourished and well-nourished subjects. Total mean level of HDL, LDL, TG and CRP had not significant correlation with plasma Se levels. There was a significant positive correlation between the mean plasma albumin and Se levels in the HD patients (P<0.05). Conclusions: The mean plasma Se level of HD patients in this area is in the normal range. There is no association between plasma Se level and malnutrition. Based on our findings, hyposelenemia is not a problem in HD patients in the Golestan Province. KEYWORDS: Selenium, Malnutrition, Inflammatory markers